Antimicrobials in Animal Agriculture in the United States: A Multidisciplinary Overview of Regulation and Utilization to Foster Collaboration: On Behalf Of the Society of Infectious Diseases Pharmacists. (12th October 2022) - Gens, Krista D; Singer, Randall S; Dilworth, Thomas J; Heil, Emily L; Beaudoin, Amanda L
Abstract: Given the complexity of antimicrobial resistance and the dire implications of misusing antimicrobials, it is imperative to identify accurate and meaningful ways to understand and communicate the realities, challenges, and opportunities associated with antimicrobial utilization and measurement in all sectors, including in animal agriculture. The objectives of this article are to ( i ) describe how antimicrobials are regulated and used in US animal agriculture and ( ii ) highlight realities, challenges, and opportunities to foster multidisciplinary understanding of the common goal of responsible antimicrobial use. Recognition of the realities of medicine, practice, and policy in the agricultural setting is critical to identify realistic opportunities for improvement and collaboration. Abstract : This article describes how antimicrobials are regulated and used in US animal agriculture and highlights realities, challenges, and opportunities to foster multidisciplinary understanding of the common goal of responsible antimicrobial use.